2012
DOI: 10.1016/j.socscimed.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pensions on health and wellbeing in rural South Africa: Does gender matter?

Abstract: Unique to Africa, a means-tested non-contributory pension is available to South Africans. In 2006, women over 60 and men over 65 were pension-eligible. To explore the effect of the pension for health and wellbeing indicators of rural South African men and women, we analyze data from the WHO-INDEPTH Study of Global Ageing and Adult Health Survey, carried out in the Agincourt sub-district by the MRC/Wits Rural Public Health and Health Transitions Research Unit (Agincourt) in 2006. Because pension receipt was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 49 publications
1
75
0
Order By: Relevance
“…The same study also found that the health status of South African women improved significantly on reaching the age of pension eligibility (Case and Wilson, 2000). The findings of the Langeberg study have been partially corroborated by separate survey of 4,085 older people in the Agincourt Health District in north east South Africa, conducted in 2006 (Schatz et al, 2012). The Agincourt data suggest that older women enjoy a “honeymoon” period in the initial years after reaching the age of pension eligibility (60 to 64), reporting higher levels of happiness and quality of life compared to those aged 55 to 59.…”
Section: Pensions and Health Theory And Evidencementioning
confidence: 71%
See 1 more Smart Citation
“…The same study also found that the health status of South African women improved significantly on reaching the age of pension eligibility (Case and Wilson, 2000). The findings of the Langeberg study have been partially corroborated by separate survey of 4,085 older people in the Agincourt Health District in north east South Africa, conducted in 2006 (Schatz et al, 2012). The Agincourt data suggest that older women enjoy a “honeymoon” period in the initial years after reaching the age of pension eligibility (60 to 64), reporting higher levels of happiness and quality of life compared to those aged 55 to 59.…”
Section: Pensions and Health Theory And Evidencementioning
confidence: 71%
“…There is considerable evidence that targeted social pensions are effective in reducing poverty among older people and their households (Barrientos et al, 2003; Long and Pfau, 2008). As with other cash transfers, it is sometimes claimed that pensions can generate other positive wellbeing outcomes, including improved health status (Case, 2001; HelpAge International, 2006, Schatz et al, 2012). The evidence to support these claims is quite limited, partly reflecting the challenges of establishing such an effect.…”
Section: Introductionmentioning
confidence: 99%
“…Deprivation and poverty are less associated with happiness 31 however, after reaching a level of care that meets basic needs, other factors, such as people's increased aspirations and concerns about their own heritage come into play 10,32 . Indeed, despite the economic changes, happiness levels have remained relatively stable in countries such as Ireland and the United States 17,33 ; a study linking retirement and welfare showed that monetary gain increased financial well-being, but the benefits of retirement on health and subjective and social welfare were transient 34 . Another binding factor between economic issues and happiness seems to be social inequality, since individuals living in areas of great social inequality tend to describe themselves as unhappy and unhealthy 35 .…”
Section: Economic Factorsmentioning
confidence: 99%
“…Gender, age and socioeconomic indicators such as income and education are factors that should be considered in research on well-being since there are a number of studies showing that men 5,6 , young adults 7 and those with higher levels of education and income tend to have higher levels of happiness and life satisfaction 8,9 .…”
Section: Introductionmentioning
confidence: 99%